Application of carbon nanotubes in perovskite solar cells: A review - Oo, T.; Debnath, Sujan (Springer New York LLC, 2017)
Solar power, as alternative renewable energy source, has gained momentum in global energy generation in recent time. Solar photovoltaics (PV) systems now fulfill a significant portion of electricity demand and the capacity of solar PV capacity is growing every year. PV cells efficiency has improved significantly following decades of research, evolving into third generations of PV cells. These third generation PV cells are set out to provide low-cost and efficient PV systems, further improving the commercial competitiveness of solar energy generation. Among these latest generations of PV cells, perovskite solar cells have gained attraction due to the simple manufacturing process and the immense growth in PV efficiency in a short period of research and development. Despite these advantages, perovskite solar cells are known for the weak stability and decomposition in exposure to humidity and high temperature, hindering the possibility of commercialization. This paper will discuss the role of carbon nanotubes (CNTs) in improving the efficiency and stability of perovskite solar cells, in various components such as perovskite layer and hole transport layer, as well as the application of CNTs in unique aspects. These includes the use of CNTs fiber in making the perovskite solar cells flexible, as well as simplification of perovskite PV production by using CNT flash evaporation printing process. Despite these advances, challenges remain in incorporation CNTs into perovskite such as lower conversion efficiency compared to rare earth metals and improvements need to be made. Thus, the paper will be also highlighting the CNTs materials suggested for further research and improvement of perovskite solar cells.